Effects of forming factors on production of wide clad aluminum alloy foils by single roll rapid solidification - HAGA, Toshio; MOTOMURA, Mitsugu (Journal of Japan Institute of Light Metals, 1989)
Production of rapidly solidified aluminum alloy clad foils with 160mm width were attempted by use of a single roll apparatus with tandem nozzles, controlling some forming factors, ie. roll speed, thickness and width of the base foil and overlying foil, order of ejection of molten alloys from two nozzles, distance between nozzles, combination of alloys for base and overlying foils. When roll speed is low or distance between nozzles is not suitable, there are cracks and disturbed layer at interface between base and overlying foils. Sound clad foil is achieved by decreasing width and thickness of overlying foils less than those of base foils. Materials and surface condition of base foils affect the surface condition of overlying foils. Combinations of alloys for base and overlying foils affect formation of crinkles of clad foil.